Pengujian Toksisitas Akut Minyak Atsiri Biji Pala pada Mencit Jantan (Mus musculus) - Ghani Abhi Majid; Yane Dila Keswara; Hery Muhamad Ansory (Jurnal Farmasi Indonesia, 2023)
Nutmeg seed essential oil works as an antibacterial, antioxidant, antifungal and anti-inflammatory. It is not yet known the safety of using nutmeg seed essential oil as a medicine so it is necessary to carry out safety tests, namely acute toxicity tests. The purpose of this study was to determine the safety of nutmeg seed essential oil and determine the LD50 value, influence on body weight, behavioral changes and macropathology of mouse organs. Isolation of nutmeg seed essential oil using the steam distillation method. Nutmeg seed essential oil was analyzed using GS-MS. Acute toxicity test in this study used fixed dose method. The test animals used 30 male white mice were divided into 6 test groups, namely the placebo control group and the treatment group given nutmeg essential oil doses of 5, 50, 300, 2000 and 5000 mg / KgBB. The observation parameters of test animals include toxic symptoms, body weight, and organ macropathology. The analysis method used is one way ANOVA followed by Tukey's Post-Hoc test. The results showed that after giving nutmeg seed essential oil there were no significant toxic effects but could affect the body weight of mice. Macropathological observation of mouse organs in all groups looked normal and no damage to mouse organs resulted from the administration of test preparations. Thus, the LD50 essential oil of nutmeg seeds is pseudo ≥ 5000 mg/KgBB, including the classification of practically non-toxic.